1986
DOI: 10.2337/diab.35.9.1034
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of Diabetes in BB Rats: I. Evidence Suggesting a Requirement for Mature T Cells in Bone Marrow Inoculum of Neonatally Injected Rats

Abstract: Injection of major histocompatibility complex (MHC)-compatible bone marrow cells from normal animals into neonatal BB rats resulted in a striking decrease in incidence of diabetes and restoration of concanavalin A (ConA) and mixed lymphocyte responses. However, injection of bone marrow cells pretreated with anti-rat thymocyte antiserum plus complement to remove mature T cells had no effect on incidence of disease, suggesting that mature T cells in the bone marrow inoculum were responsible for prevention of dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
20
1

Year Published

1987
1987
2005
2005

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 17 publications
(22 reference statements)
0
20
1
Order By: Relevance
“…Neonatal inoculation of diabetes-prone BB rats with bone marrow cells from a normal strain of rat (creating chimeras) prevents diabetes [6,12,[19][20][21]. In our study [6], mixed lymphocyte cultures and ConA stimulation assays performed with lymphocytes from the recipient BB rats demonstrated that they had been immunologically reconstituted. Diabetes in the BB rat can be prevented or reversed by various immunosuppressive procedures, such as administration of antilymphocyte globulin [22], glucocorticoids [23], or cyclosporin [23-251. A series of bone marrow irradiation chimeras were constructed [26,27], using various combinations of normal or BB rat recipients and bone marrow donors, in an attempt to determine the site of the defect(s) leading to diabetes and/or T-cell lymphopoenia in the BB rat.…”
mentioning
confidence: 53%
See 4 more Smart Citations
“…Neonatal inoculation of diabetes-prone BB rats with bone marrow cells from a normal strain of rat (creating chimeras) prevents diabetes [6,12,[19][20][21]. In our study [6], mixed lymphocyte cultures and ConA stimulation assays performed with lymphocytes from the recipient BB rats demonstrated that they had been immunologically reconstituted. Diabetes in the BB rat can be prevented or reversed by various immunosuppressive procedures, such as administration of antilymphocyte globulin [22], glucocorticoids [23], or cyclosporin [23-251. A series of bone marrow irradiation chimeras were constructed [26,27], using various combinations of normal or BB rat recipients and bone marrow donors, in an attempt to determine the site of the defect(s) leading to diabetes and/or T-cell lymphopoenia in the BB rat.…”
mentioning
confidence: 53%
“…Neonatal inoculation of diabetes-prone BB rats with bone marrow cells from a normal strain of rat (creating chimeras) prevents diabetes [6,12,[19][20][21]. In our study [6], mixed lymphocyte cultures and ConA stimulation assays performed with lymphocytes from the recipient …”
mentioning
confidence: 80%
See 3 more Smart Citations